Analisis Manajemen Pendidikan di SMP N 27 Medan: Studi Efektivitas dan Efisiensi Pengelolaan Sekolah - Sani Susanti; Nayla Rafa Agasti; Indah Melbrina Br Milala; Renata Dinda Sihombing; Wanda Christiani Sitompul (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Management is a very important process in an organization, especially in the field of education. Management can help create a conducive environment for students, improve the quality of education, and achieve the desired educational goals. Therefore, this research aims to increase the effectiveness and efficiency of the education system at SMP N 27 Medan through the implementation of effective and sustainable education management. Educational management is considered a process consisting of several stages, namely planning, organizing, directing and controlling. The techniques used in this research are theoretical and literature analysis methods, as well as data collection through surveys and observations. The research results show that the majority of teachers at SMP N 27 Medan feel that the education and management system in their school is quite effective and efficient. However, there are several areas that require further improvement or improvement. This research shows that effective education management must focus on improving the quality of teaching staff, utilizing technology to increase access and effectiveness of learning, and strengthening the bureaucratic system to make it more efficient and responsive to educational needs. In this way, the education system at SMP N 27 Medan can run more effectively and efficiently, as well as improve the quality of education, effectiveness of learning and the quality of teaching staff.